Morphology of powerful suction organs from blepharicerid larvae living in raging torrents - Richard Johnston (BMC Zoology, 2019)
BackgroundSuction organs provide powerful yet dynamic attachments for many aquatic animals, including octopus, squid, remora, and clingfish. While the functional morphology of suction organs from some cephalopods and fishes has been investigated in detail, there are only few studies on such attachment devices in insects. Here we characterise the morphology and ultrastructure of the suction attachment organs of net-winged midge larvae (genus Liponeura; Diptera: Blephariceridae) – aquatic insects that live on rocks in rapid alpine waterways where flow speeds can reach 3 m s− 1 – using scanning electron microscopy, confocal laser scanning microscopy, and X-ray computed micro-tomography (micro-CT). Furthermore, we study the function of these organs in vivo using interference reflection microscopy.ResultsWe identified structural adaptations important for the function of the suction attachment organs in L. cinerascens and L. cordata. First, a dense array of spine-like microtrichia covering each suction disc comes into contact with the substrate upon attachment, analogous to hairy structures on suction organs from octopus, clingfish, and remora fish. These spine-like microtrichia may contribute to the seal and provide increased shear force resistance in high-drag environments. Second, specialised rim microtrichia at the suction disc periphery were found to form a continuous ring in close contact and may serve as a seal on a variety of surfaces. Third, a V-shaped cut on the suction disc (“V-notch“) is actively opened via two cuticular apodemes inserting on its flanks. The apodemes are attached to dedicated V-notch opening muscles, thereby providing a unique detachment mechanism. The complex cuticular design of the suction organs, along with specialised muscles that attach to them, allows blepharicerid larvae to generate powerful attachments which can withstand strong hydrodynamic forces and quickly detach for locomotion.ConclusionThe suction organs from Liponeura are underwater attachment devices specialised for resisting extremely fast flows. Structural adaptations from these suction organs could translate into future bioinspired attachment systems that perform well on a wide range of surfaces.